In Situ Observation of Cu–Ni Alloy Nanoparticle Formation by X‐Ray Diffraction, X‐Ray Absorption Spectroscopy, and Transmission Electron Microscopy: Influence of Cu/Ni Ratio. Issue 1 (4th December 2013) - Wu, Qiongxiao; Duchstein, Linus D. L.; Chiarello, Gian Luca; Christensen, Jakob M.; Damsgaard, Christian D.; Elkjær, Christian F.; Wagner, Jakob B.; Temel, Burcin; Grunwaldt, Jan‐Dierk; Jensen, Anker D.
Abstract Silica‐supported, bimetallic Cu–Ni nanomaterials were prepared with different ratios of Cu to Ni by incipient wetness impregnation without a specific calcination step before reduction. Different in situ characterization techniques, in particular transmission electron microscopy (TEM), X‐ray diffraction (XRD), and X‐ray absorption spectroscopy (XAS), were applied to follow the reduction and alloying process of Cu–Ni nanoparticles on silica. In situ reduction of Cu–Ni samples with structural characterization by combined synchrotron XRD and XAS reveals a strong interaction between Cu and Ni species, which results in improved reducibility of the Ni species compared with monometallic Ni. At high Ni concentrations silica‐supported Cu–Ni alloys form a homogeneous solid solution of Cu and Ni, whereas at lower Ni contents Cu and Ni are partly segregated and form metallic Cu and Cu–Ni alloy phases. Under the same reduction conditions, the particle sizes of reduced Cu–Ni alloys decrease with increasing Ni content. Estimates of the metal surface area from sulfur chemisorption and from the XRD particle size generally agree well on the trend across the composition range, but show some disparity in terms of the absolute magnitude of the metal area. This work provides practical synthesis guidelines towards preparation of Cu–Ni alloy nanomaterials with different Cu/Ni ratios, and insight into the application of different in situ techniques for characterization of the alloy formation.